A case study on the interior design of a selected mall in Quezon City addressing the spatial needs of senior citizens - Garcia, Kristine C. (College of Home Economics, University of the Philippines Diliman, 2013)
ABSTRACT This research which utilized the case study approach sought to determine the spatial needs of senior citizens in a selected mall in Quezon City and to evaluate the mall's interior design if such spatial needs are being addressed. The data gathering procedures were done in three stages namely, 1) a pretest survey conducted among at least fifteen senior citizen respondents, 2) a focus group discussion and survey among eight senior citizens and 3)observation through photographs. Participants for both the survey and focus group discussion were chosen using purposive sampling based on the following selection criteria: Filipino senior citizens, ages 60 and above, who still have the physical strength to visit public establishments such as malls. Instruments used include two sets of questionnaire, guide questions for focus group discussion, pens, paper, and a cellphone used as a camera and voice recorder. The study focused on the following two public areas in the mall: (1) the Walkways and Corridors and (2) the Restrooms. Results showed that all spatial aspects of Walkways and Corridors included in this study such as lighting, layout clarity, acoustics and flooring were rated "average" or better except for signs/wayfinding, which was rated "fair". For the Restrooms, the spatial aspects studied were lighting, signs/wayfinding, anthropometrics, and flooring; all were rated "average" or better. The findings suggest that the selected mall generally addresses the needs of senior citizens, particularly on the aspects of interior design included in this study. The participants, however, strongly suggested that certain elements in the public areas be added or changed such as more benches, improved signs, and better lighting. The study recommends further studies that will look into the spatial needs of senior citizens in public space such as malls.